2013
DOI: 10.1109/twc.2013.072513.121945
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Power Randomization for the Minimization of Outage Probability

Abstract: Abstract-The optimum power randomization problem is studied to minimize outage probability in flat block-fading Gaussian channels under an average transmit power constraint and in the presence of channel distribution information at the transmitter. When the probability density function of the channel power gain is continuously differentiable with a finite second moment, it is shown that the outage probability curve is a nonincreasing function of the normalized transmit power with at least one inflection point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…where λ i is the channel switching factor for channel i and P c,i is the average probability of correct decision over channel i for a power level of P i , which can be calculated as P c,i = 1 − g i (P i ) (9) with g i (P i ) denoting the average probability of symbol error as computed in (4)-(6) for different types of modulations and cases. The expression in (8) corresponds to the average number of symbols that are correctly received during the communication interval of length λ i T .…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…where λ i is the channel switching factor for channel i and P c,i is the average probability of correct decision over channel i for a power level of P i , which can be calculated as P c,i = 1 − g i (P i ) (9) with g i (P i ) denoting the average probability of symbol error as computed in (4)-(6) for different types of modulations and cases. The expression in (8) corresponds to the average number of symbols that are correctly received during the communication interval of length λ i T .…”
Section: Remarkmentioning
confidence: 99%
“…Time sharing (randomization) has attracted a significant deal of interest in the literature due to its capability to provide performance improvements for communication systems [1][2][3][4][5][6][7][8][9][10][11]. In [2], it is demonstrated that the average probability of error over additive noise channels with arbitrary noise probability density functions (PDFs) can be reduced via optimal stochastic signaling, which performs time sharing among at most three different signal levels for each information symbol.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed algorithm leads to a near-optimal capacity that is achieved without antenna selection. In addition to the capacity, other metrics such as probability of error, probability of detection, and outage probability are considered in various resource allocation problems; e.g., [7]- [15]. For example, in the detector randomization problem, the aim is to minimize the average probability of error of a communication system by optimizing time sharing factors and transmit power (signal) levels corresponding to different detectors at the receiver [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, benefits of randomization (or, time-sharing) have been studied for various detection and estimation problems in the literature [1]- [13]. For instance, in the context of noise enhanced detection and estimation, an additive "noise" component that is realized by a randomization among a certain number of signal levels can be injected into the input of a suboptimal detector or estimator for performance enhancement [1]- [5].…”
Section: Introductionmentioning
confidence: 99%